Metabolism and pharmacokinetic study of deuterated osimertinib. (3rd February 2023) - Zhan, Xuyi; Bao, Shaoyin; Li, Xumei; Zhou, Shaojun; Dahar, Maha Raja; Lin, Nengming; Chen, Xiugui; Niu, Chengshan; Ji, Kaige; Wu, Yusheng; Zeng, Kui; Tang, Zhihua; et al.
Abstract: Osimertinib is a highly selective third‐generation irreversible inhibitor of epidermal growth factor receptor mutant, which can be utilized to treat non‐small cell lung cancer. As the substrate of cytochrome P450 enzyme, it is mainly metabolized by the CYP3A enzyme in humans. Among the metabolites produced by osimertinib, AZ5104, and AZ7550, which are demethylated that is most vital. Nowadays, deuteration is a new design approach for several drugs. This popular strategy is deemed to improve the pharmacokinetic characteristics of the original drugs. Therefore, in this study the metabolism profiles of osimertinib and its deuterated compound (osimertinib‐d3) in liver microsomes and human recombinant cytochrome P450 isoenzymes and the pharmacokinetics in rats and humans were compared. After deuteration, its kinetic isotope effect greatly inhibited the metabolic pathway that produces AZ5104. The plasma concentration of the key metabolite AZ5104 of osimertinib‐d3 in rats and humans decreased significantly compared with that of the osimertinib. This phenomenon was consistent with the results of the metabolism studies in vitro. In addition, the in vivo results indicated that osimertinib‐d3 had higher systemic exposure (AUC) and peak concentration (Cmax ) compared with the osimertinib in rats and human body. Abstract : (1) The LC‐MS/MS method can effectively determine substrates and their metabolites. (2) Kinetic isotope effect greatly inhibited the metabolism of osimertinib‐d3. (3) Osimertinib‐d3 had higher AUC and Cmax compared with osimertinib in rats and humans.